PENGARUH MODAL INTELEKTUAL TERHADAP MANAJEMEN LABA RIIL DAN FUTURE STOCK RETURNS - Tendy Wato (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2016)
This study aims to examine the influence of Intellectual Capital (IC) on Real Earnings Management (MR) and Future Stock Returns (FSR) in the manufacturing companies listed in Indonesia Stock Exchange (IDX). The data used was obtained using multiple regression of 27 companies manufacturing for the period 2007 to 2013. Model IC using VAICTM of Pulic (2000), Model Manajemen Laba Riil (MR) of Roychowdhury (2006) and the FSR of Sloan (1996). Model analysis of the test data is performed by Multiple Regression. The results showed a partial effect on the IC to MR- PROD, MR-DISX and MR-CFO. IC has affect the FSR significantly. The overall results of this study support the theory resourced-based and knowledge-based. Research of Intellectual Capital (IC) is a new one in Indonesia, so that the data associated with the IC is still difficult to obtain. Also there is no official standard referenced in particular the Financial Accounting Standards (IFRSs) Indonesia in calculating the IC. The paper shows that intellectual capital is an important element affecting the future stock returns with real earnings management as intervening. The paper’s finding suggest that it is necessary to improve the transparency of the accounting information, so as to reduce real earnings management, especially in cash flow operation and improve earnings quality to some extent, which provides valuable reference for the company’s decision. This paper extends prior research by addressing the potential effects of IC on future stock returns with real earnings management as intervening. The findings reported in this paper provide novel insights to the empirical financial accounting literature.Keyword: Intellectual capital, real earning management, future stock returns.